Comparison of PGRI Course Study Results Using Google Meet vs. Zoom Meetings - Surmana, Surmana; Hamzah, Syukri (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study was to compare the outcomes of student’s instruction in the PGRI course Semester 1 PGSD Study Program, Universitas PGRI Palembang, using Google Meet and Zoom meetings. The research method is quantitative, and the formula for the independent t-test is used (unpaired t-test). In this study, 81 students were sampled, with 40 using Google Meet in 1.Q and 41 using Zoom Meeting in 1.R. data collection instruments included documentation, observation, and tests. The findings revealed a significant difference in learning outcomes between the Google Meet application and Zoom Meeting in the PGRI course at the Universitas PGRI Palembang's PGSD study program. According to the findings of this study, using Google Meet is superior to using Zoom Meeting.